David Delfín and the Art as a Guaranty of Mental Health - Amaro Martos, Ismael (Eikón / Imago, 2019)
Louise Bourgeois’s statement “l’art est une garantie de santé mentale” has been an inspiration for this research which addresses to deepen in the leading figure of the designer David Delfín. This study would show some accurate moments of his life in order to understand his legacy. As a faithful follower of Freud’s psychoanalytic theories and the passion which the surrealists had for their ‘patron saint’ it would be plausible parlance about emotions, as Bourgeois did, unconscious, that each of the collections which constitute the career path of David Delfin have been tacitly acknowledged by public.